Tissue-Specific Immunity in Osteoarticular Tuberculosis - Sethy, Siddharth Sekhar; Deep, Gagan; Sudhakar, P. V.; Goyal, Tarun; Kandwal, Pankaj; Arora, Shobha (Indian journal of orthopaedics, 2025)
Introduction Osteoarticular TB contributes to roughly 10% of the cases of extrapulmonary TB. The incidence of osteoarticular tuberculosis is one of the lowest in extrapulmonary tuberculosis, probably only next to cutaneous tuberculosis in non-HIV patients. Considering the low incidence of primary osteoarticular tuberculosis without pulmonary tuberculosis, we hypothesise that there is an element of tissue-specific immunity against tuberculosis in the body, which appears to be very high in bone and joints. The concept of immunity against tuberculosis in general is well-established for pulmonary tuberculosis but not so for osteoarticular tuberculosis. Materials and methods A literature search was carried out using the online databases PubMed, EMBASE, and the Cochrane database for all studies published in the English language from May 2000 to September 2020. We compiled the available information in the literature related to the subject to analyse the concept of tissue-specific immunity for osteoarticular tuberculosis. Results 24 studies were included in the review. Bone receives less proportion of total body blood flow when compared to other organs. Lungs, the gastrointestinal system, and the urinary system receive a significantly higher proportion of total body blood flow than bones. This may decrease the chances of haematogenous spread of mycobacterium bacilli to bones rather than other systems. On the receptor level, T cells express a prolyl-hydroxylase domain (PHD) on their surface, which plays a pivotal role in orchestrating the effects of oxygen tension on immune response and T cell proliferation. In oxygen-replete states such as in the lungs, the PHD domain on the T-cells senses the high oxygen concentration and initiates the degradation of the hypoxia-inducible factor-1α (HIF-1α). The major role of HIF-1α is to downregulate the T regulatory cells and activate the Th-1 cells. The main function of Th-1 cells is to promote a cell-mediated immune response that is required for host defence against intracellular microbes. Vice versa happens in oxygen-depleted states, as in bones, more so in cortical bones. Our observations show that tuberculosis of long bones is uncommon compared to cancellous bone tuberculosis. The highest concentration of CD-4 cells is found in lymphoid tissue, followed by bone marrow, and the lowest is in the lungs. Tissue concentration of CD4 cells may be an important but not the sole factor responsible for immunity against MTb. The incidence of tubercular lymphadenitis is quite high despite the presence of a high amount of CD4 cells there. The submucosal layer of the GI tract is rich in lymphoid tissue. The GI tract receives a high proportion of cardiac output, but the incidence of GI tuberculosis is quite low. This may partially be due to the high amount of lymphoid tissue rich in CD4 cells in the intestine. Similarly, bone marrow has a high amount of CD4 cells, and this may be an important factor in providing local immunity to skeletal tuberculosis. Conclusion Factors like a low proportion of cardiac output to bones, oxygen-deplete microenvironment there, and a high amount of CD4 cells may be responsible for the low incidence of osteoarticular tuberculosis. However, it needs further research on the molecular level.